Evidence Of Adultery According To Qanun Jinayah No. 6 Of 2014 And Syafi'iyah Fiqh - Abdullah Abdullah (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
This article aims to provide a comparison between the Aceh Qanun Jinayah and Shafi'iyah Jurisprudence, as implemented in Aceh. What are the provisions regarding evidence of adultery in Qanun No. 6 of 2014 and Shafi'iyah Jurisprudence, and what are the differences between the two? To obtain these answers, this research is a qualitative descriptive study using library research techniques (library research). All sourcesdata obtained from literature available in the library. The method used to analyze data is descriptive analysis and interpretation methods. The descriptive analysis method is a method used in writing by presenting the data obtained and the problems that arise to be analyzed according to the discussion. Meanwhile, the interpretation method is drawing conclusions from the author's own understanding of the opinions quoted from a reference. The results of this research are that the evidence of adultery contained in qanun jinayah no. 6 of 2014 is the result of a combination of schools of jurisprudence including Shafi'i jurisprudence. However, the qanun jinyah does not contain in detail the criteria that will be used as evidence of adultery, in contrast to the Syafi'i fiqh which explains it in detail. Then in qanun jinayah no. 6 of 2014 added that DNA test results are evidence of adultery for pregnant women and these results are not found in Syafi'i jurisprudence.